2-Deoxy-D-Glucose: A Novel Pharmacological Agent for Killing Hypoxic Tumor Cells, Oxygen Dependence-Lowering in Covid-19, and Other Pharmacological Activities. (2nd March 2023) - Singh, Raman; Gupta, Vidushi; Kumar, Antresh; Singh, Kuldeep
Abstract : The nonmetabolizable glucose analog 2-deoxy-D-glucose (2-DG) has shown promising pharmacological activities, including inhibition of cancerous cell growth and N-glycosylation. It has been used as a glycolysis inhibitor and as a potential energy restriction mimetic agent, inhibiting pathogen-associated molecular patterns. Radioisotope derivatives of 2-DG have applications as tracers. Recently, 2-DG has been used as an anti-COVID-19 drug to lower the need for supplemental oxygen. In the present review, various pharmaceutical properties of 2-DG are discussed.